Evaluation of comparative hepatoprotective activity of organic versus non-organic Camelia sinensis methanol extracts in albino mice - Dipendra Khadka; Pramod Aryal; Daya Ram Parajuli; Anita Shah; Narayan Gautam; Shailendra Dhakal; Bal Krishna Adhikari (Al Ameen Medical College, 2019)
Objectives: The study was carried out to compare hepatoprotective activity of organic versus non organic Camelia sinensis methanol extracts in albino mice. Materials and Methods: In vivo hepatoprotective activity of methanol extracts of organic and non-organic Camelia sinensis extracts (200 and 400 mg/kg) were evaluated using experimental CCl4 induced toxicity model. The mice were divided into seven group (n=6). The mice were administered once daily with 10% DMSO (negative control), 25 mg/kg Silymarin (positive control), organic tea methanol extracts (200mg/kg, 400mg/kg) and nonorganic tea methanol extracts (200mg/kg, 400mg/kg) for seven days followed by the hepatotoxicity induction using carbontetrachloride. The blood samples were collected and subjected to biochemical analysis. In addition, histopathological examination of the hepatocytes was performed to observe any damage in a cellular level. Ballooning degeneration, cytic necrosis, confluent necrosis, submassive necrosis, micro and macro vesicular steatosis, lymphocyte infiltration were observed in the treatment and CCl4 induced toxicity model. Results: Severe hepatic damage due to CCl4 was indicated by significant increase in the liver enzymes level including Aspartate Aminotransferase (AST), Alanine Aminotransaminase (ALT) and Alkaline Phosphatase (ALP). The elevated levels of these enzymes were reduced in a dose-dependent manner in biochemical analysis by the organic and nonorganic tea methanol extracts. The reduction of liver enzymes level is better in organic treated mice than that of non-organic treated mice. Mice injected with CCl4 have ballooning degeneration with confluent necrosis along with mixed infiltration of inflammatory cells which represents that the liver is highly injured. However, the organic extracts treated mice showed potent hepatoprotective effect with minimal focal ballooning degeneration indicating that the hepatocytes morphology resembling towards normal. Interestingly, the non-organic extracts showed a hepatoprotective effect but there are massive micro-vesicular steatosis and focal lymphocytes. We found a superior hepatoprotective activity of organic extracts than that of non-organic extracts. The liver injury produced by CCl4 has been reversed by the Silymarin which is the positive control in the experiment. Conclusion: The study revealed that the hepatoprotective activity of organic Camelia sinensis is better than the non organic Camelia sinensis.